2005
DOI: 10.1002/glia.20232
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ inhibits cell cycle exit in differentiating oligodendrocyte progenitor cells

Abstract: The developmental processes of the oligodendrocyte progenitor cell (OPC) lineage that are targeted by interferon-gamma (IFN-gamma) were studied in primary rat OPC cultures. Under conditions of thyroid hormone-mediated oligodendrocyte differentiation, IFN-gamma produced a dose-dependent apoptotic response in OPCs. The lowest dose tested (15 ng/ml or 75 U/ml) was nonapoptotic, but activated detectable STAT1 DNA-binding. At this dose, IFN-gamma reduced the percentage of mature O1+ cells and increased the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
85
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 105 publications
(100 reference statements)
12
85
2
1
Order By: Relevance
“…[3][4][5]59,60 The latter (IFN-g)was shown to inhibit cell cycle exit in oligodendrocyte progenitor cells and attenuate MBP expression. 61 Taken together, these previous data point to an alternative view that activated astrocytes and microglia in brains of CPZ-treated mice may contribute to or exacerbate mature oligodendrocyte loss and myelin breakdown as shown in this study. It implies that antiinflammatory treatment or inhibiting astrocyte and microglia activation may be of help in improving the CPZinduced white matter damage.…”
Section: Flavopiridol Alleviated Cpz-induced Activation Of Astrocytessupporting
confidence: 84%
“…[3][4][5]59,60 The latter (IFN-g)was shown to inhibit cell cycle exit in oligodendrocyte progenitor cells and attenuate MBP expression. 61 Taken together, these previous data point to an alternative view that activated astrocytes and microglia in brains of CPZ-treated mice may contribute to or exacerbate mature oligodendrocyte loss and myelin breakdown as shown in this study. It implies that antiinflammatory treatment or inhibiting astrocyte and microglia activation may be of help in improving the CPZinduced white matter damage.…”
Section: Flavopiridol Alleviated Cpz-induced Activation Of Astrocytessupporting
confidence: 84%
“…However, IFN-␥ mRNA was not detectable in all mice, and the fold increase was small. Other studies have demonstrated that IFN-␥ can both inhibit differentiation and induce apoptosis of OPCs, 60,61 as well as protect mature oligodendrocytes against cuprizone-induced destruction 62 and inflammatory destruction, 63 which suggests that the effect of IFN-␥ on the oligodendrocyte population is context-dependent. However, although our finding of a several hundred-fold increase in IFN-␥ mRNA expression in the PP-lesioned T PLP mice raises the possibility of a role for IFN-␥ in the oligodendrotrophic effect of the myelin-reactive T cells, it is noteworthy that IFN-␥ mRNA detectable via in situ hybridization was expressed by rare cells, presumed to be T cells, located outside of the molecular layer of the dentate gyrus.…”
Section: Discussionmentioning
confidence: 97%
“…Studies using purified oligodendrocytes in vitro, however, suggest that the cytokine may have a direct, harmful effect on oligodendrocytes (Torres et al, 1995;Agresti et al, 1996;Andrews et al, 1998;Baerwald and Popko, 1998;Lin et al, 2005). IFN-␥ has been shown to inhibit cell cycle exit of oligodendroglial progenitor cells, which may predispose these cells to apoptotic death (Chew et al, 2005). Additionally, IFN-␥ has been shown to be a very powerful apoptosis-inducing agent for developing oligodendrocytes (Baerwald and Popko, 1998;Baerwald et al, 2000;Lin et al, 2005).…”
Section: Discussionmentioning
confidence: 99%